2002
DOI: 10.1603/0022-2585-39.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Acari Ectoparasites of Bats from Minas Gerais, Brazil: Table 1

Abstract: Ectoparasites were recovered from Brazilian bats captured from April to November 1997 at or near Parque Estadual do Rio Doce, State of Minas Gerais, southeastern Brazil. Sixty bats were collected, representing three families and 13 species. Five Acari families were recorded: Myobiidae, Trombiculidae, Labidocarpidae, Macronyssidae, and Spinturnicidae. The macronyssid Radfordiella desmodi Radovsky (71 specimens) and the spinturnicid Periglichrus iheringi Oudemans (45 specimens) were the most abundant mite specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…Given this wide range of hosts, it is possible that P. iheringi in fact comprises a number of species (HERRIN & TIPTON, 1975). In Brazil, this mite has been reported in Artibeus lituratus (GETTINGER & GRIBEL, 1989;DANTAS-TORRES et al, 2009;SILVA et al, 2009;ALMEIDA et al, 2011;CONFALONIERI, 1976) (AZEVEDO et al, 2002;ALMEIDA et al, 2011;DANTAS-TORRES et al, 2009;CONFALONIERI, 1976).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Given this wide range of hosts, it is possible that P. iheringi in fact comprises a number of species (HERRIN & TIPTON, 1975). In Brazil, this mite has been reported in Artibeus lituratus (GETTINGER & GRIBEL, 1989;DANTAS-TORRES et al, 2009;SILVA et al, 2009;ALMEIDA et al, 2011;CONFALONIERI, 1976) (AZEVEDO et al, 2002;ALMEIDA et al, 2011;DANTAS-TORRES et al, 2009;CONFALONIERI, 1976).…”
Section: Resultsmentioning
confidence: 91%
“…In Brazil, it has been reported in association with C. perspicillata in the state of Pernambuco (DANTAS-TORRES et al, 2009), S. tildae in Espírito Santo (CONFALONIERI, 1976) and with S. lilium in Brasília (GETTINGER & GRIBEL, 1989), Minas Gerais (CONFALONIERI, 1976;AZEVEDO et al, 2002) and Rio de Janeiro (CONFALONIERI, 1976;ALMEIDA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most information about 10 species of Periglischrus and one of Spinturnix recorded in Brazil comprises geographic and host occurrences (Confalonieri 1976, Azevedo et al 2002, Graciolli et al 2008, Silva et al 2009). Only Gettinger and Gribel (1989), Dantas-Torres et al (2009) and Almeida et al (2011) showed at least one parasitological index (prevalence and/or intensity/abundance sensu Bush et al (1997)) for spinturnicid mites on their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Apenas recentemente alguns estudos foram feitos no Brasil inventariando a fauna regional de ácaros associados a morcegos (Gettinger & Gribel, 1989;Azevedo et al, 2002;Dantas-Torres et al, 2009;Silva et al, 2009;Almeida, et al, 2011).…”
unclassified